Kesan Visual Make-Up Special Effect sebagai Elemen Penguat Suspense Dalam Film Abadi Nan Jaya - Mela Harmalya; Edy Suisno (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to analyze the visual impression of special effects makeup as a suspense-enhancing element in Abadi Nan Jaya directed by Kimo Stamboel. This research employs a descriptive qualitative method with a film analysis approach. Data were collected through observation of scenes featuring special effects makeup and supported by relevant literature. The findings reveal that special effects makeup plays a significant role in building, developing, and maintaining suspense throughout the narrative through three main phases: the emergence of threat, the spread of threat, and the experience of loss and despair. In the first phase, the characters’ physical transformations create impressions of abnormality, disturbance, and danger that generate curiosity and anxiety among viewers. In the second phase, visual depictions of wounds, blood, bodily damage, and zombie transformations affecting multiple characters strengthen the perception of a spreading outbreak. In the third phase, the physical deterioration of the main characters creates impressions of loss and despair, increasing the audience’s emotional engagement. Furthermore, visual elements such as open wounds, body decay, and physical deformities produce horror impressions consistent with Carroll’s concept of art-horror, characterized by the presence of something both dangerous and unnatural. Therefore, special effects makeup functions not only as an aesthetic component but also as a cinematic element that contributes to the construction of suspense and enhances the audience’s emotional experience in Abadi Nan Jaya.